Comparative analyses of helical properties in asymmetric 1, 2-diacyl-sn-glycerols by means of circular dichroism and proton NMR spectroscopies: notable effects of substituting groups at sn-3 position. Issue 20 (1st November 2015) - Yuan, Mengfei; Fukuda, Kazuo; Dohi, Hirofumi; Uzawa, Hirotaka; Nishida, Yoshihiro
Graphical abstract